Departamento de relações com investidores (ri): um estudo sobre o atendimento do Rinas Empresas de Capital aberto do Brasil - Kunst, Rosane (Universidade do Vale do Rio dos Sinos, 2012)
Currently the capital market believes that issues such as transparency, fairness, best corporate governance, accounts installment and sustainability are essential for a company lead in market, becauseofthis, becomes essential the Department Investor Relations (DIR) work. Considering this, the main objective of this research is to analyze the performance of the DIR activities, according to the theexpectationsof itsstrategic public. The new era of communication in the capital market companies require special care when interacting with their audiences. An online questionnaire was applied to these stakeholders which revealed two groups of sampling, the first of several companies includes shareholders, market analysts and other investors in the market, and the second is composed by shareholders and investors of just one company. The results of the survey questions are presented in tables and charts, where it can be seen that 70% of the public are satisfied with the company's IR, and some activities, such as information dissemination and communication tools should be improved in the attendance´s IR. It is suggested for future work the application of research for samples of equivalent public because comparisons may be more accurate.
Keywords: Relações com investidores; Divulgação de informações; Ferramentas de comunicação; Governança corporativa; Investor relations; Disclosure; Communication tools; Corporate governance